(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: The space occupied by religions of African matrix in Brazil is expressive when it comes to mutual aid practices. Their contributions to solidarity processes and to overcome problems of material and spiritual nature faced by individuals, either faithful, or not, deserves special attention. Objective: Seize Candomblé Temples as social agencies and their relationship with different social sectors to promote citizenship, even in the field of health. Methods: References to the theme were identified and added with ethnographies of Temples from Rio de Janeiro and Salvador in order to analyze data on social actions taken at these religious spaces. Results: Initiatives such as social projects, cultural programs and health fairs are significant actions to design communication paths with society in general. These actions seek to socially legitimize these religious temples as social agencies, as well as to weave mechanisms to preserve such complex system of practices and their unique knowledge. Conclusion: Legitimizing these Temples as sacred and socially multiple and diverse spaces, as well as acknowledging their respective social actors are actions that must be anchored in communicative practices that increasingly reinforce their spaces of speech. These actions also reinforce their ancestrality and successful experiences with local communities.